Segurança pública: dever do Estado: garantia do exercício da cidadania - Gerônimo, Gislene Donizetti (2011)
The Modern State appeared as a new type of State. Characterized for the sovereign power, it was instituted to assure the order and the peace in the State community, as well as providing a legal communitarian order in which the individuals could exert their basic rights and lived with dignity. In this way, the State it is constructed to guarantee to the individual the security to live in society, endorsed by laws which could provide the full exercise of their personal rights. The Modern State appears as a Liberal State or 'Rule of Law', characterized for the legal limitation of State power. It is followed by the Social State, and, later, for the Democratic State of Law, characterized for the consecration of the human rights and by the popular sovereignty. Amongst the consecrated human rights, we also could find the right to the public security which, by the way, always was present in the history of the human kind and in all of the Brazilian Constitutions. The Federal Constitution of Brazil in 1988, regulated the public security as a basic right in its article 5º, also as social right in its article 6º and as a State duty and a responsibility of the brazilian society in its article 144, in which regulated the responsible of police agencies for the exercise of the public security. Still thus, the public security is exerted by agencies that had not been regulated in the Constitution, what generates relative debate which also occur, even though, for the incapacity of the policies constitutionally established in consequence of the highest index of existing crime in our Country. Thus, it is necessary joint action of the State Powers, through its Executive, Legislative and Judiciary branches, and also by the society, in order to elaborate and implement public policies towards the public security, that could contribute to prevent and to contain crime.